Neoplastic-like transformation effect of single-walled and multi-walled carbon nanotubes compared to asbestos on human lung small airway epithelial cells. Issue 5 (August 2014) - Wang, Liying; Stueckle, Todd A.; Mishra, Anurag; Derk, Raymond; Meighan, Terence; Castranova, Vincent; Rojanasakul, Yon
Abstract Accumulating evidence indicates that carbon nanotubes (CNTs) are biopersistent and can cause lung damage. With similar fibrous morphology and mode of exposure to asbestos, a known human carcinogen, growing concern has arisen for elevated risk of CNT-induced lung carcinogenesis; however, relatively little is known about the long-term carcinogenic effect of CNT. Neoplastic transformation is a key early event leading to carcinogenesis. We studied the ability of single- and multi-walled CNTs to induce neoplastic transformation of human lung epithelial cells compared to asbestos. Long-term (6-month) exposure of the cells to occupationally relevant concentrations of CNT in culture caused a neoplastic-like transformation phenotype as demonstrated by increased cell proliferation, anchorage-independent growth, invasion and angiogenesis. Whole-genome expression signature and protein expression analyses showed that single- and multi-walled CNTs shared similar signaling signatures which were distinct from asbestos. These results provide novel toxicogenomic information and suggest distinct particle-associated mechanisms of neoplasia promotion induced by CNTs and asbestos.